The role of literacy culture in improving students' learning outcomes at elementary school - Brilliananda, Cindy Cindhana; Siregar, Dina Shabrina Putri; Muktamaroh, Asna Istikmalatul; Rahaya, Ivana Septia; Nasution, Dea Yuanita (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
The School Literacy Movement (Gerakan Literasi Sekolah, GLS) has been implemented in Indonesia for nearly nine years, and its effectiveness needs to be evaluated. This study aims to determine the correlation between literacy activities and students’ academic achievement at SDN Bojasari Wonosobo. A descriptive quantitative approach was used, involving 58 students from grades IV and V as participants. Data were collected through questionnaires, interviews, observations, and documentation. The results indicate that literacy activities do not significantly influence students’ academic achievement. The literacy program was found to be less effective due to the following factors: (1) students focus more on summarizing than on understanding the content, (2) not all teachers provide follow-up activities, either written or verbal, (3) some students lack the ability to apply reading strategies, (4) many students do not use appropriate strategies to comprehend texts, and (5) few students use non-textbook resources to enrich their knowledge.